ARRANGEMENT OF ABANDONED LAND IN INDONESIA - widyatmojo, s. jati (Pusat Unggulan Ipteks-PUI Universitas Jambi, 2023)
And in a country cannot be owned, controlled, and used freely by humans but is bound by the provisions stipulated by the government or the State as the ruler of general rights regulated by the State in the agrarian law. The granting of rights by the State in the form of certificates of land rights must be balanced with strict provisions on the obligations of the holder of land rights. Rights and obligations appear together. Rights and obligations arise at the same time. Although their nature is different and opposite, their existence cannot be separated. The State has experienced many difficulties in controlling the neglect of land rights, especially those with ownership certificates. There is much speculation by individuals or legal entities that make Land an object of investment, especially land with property rights, because it has a more substantial and fuller legal force than other land rights recognized by the State. It was not utilizing the Land optimally because it is used as an investment object, so it is neglected. Abandoned Land is a violation of the law, so the form of controlling abandoned Land is the principle of legal certainty. Law enforcement on abandoned Land is the personification of the State for law violators who are detrimental to the nation, State, and people of Indonesia. Private rights granted by the State are more substantial and fuller in terms of property rights granted by the State because of their nature regulated by law. The ambiguity of the norms governing the criteria for abandoned land results in the difficulty of the State being able to prove a land as abandoned Land. The State is still focused on controlling other primary land rights. This can be seen from the different criteria for controlling land ownership rights with other primary land rights when viewed from the arrangement. It is necessary to regulate abandoned Land, which is more emphasized in land laws and regulations under the principles of good legislation so that it can be implemented as a form of law enforcement by the State. Whereas the purpose of the stipulation of abandoned Land is that Land that is not cultivated according to the granting of its rights can be used as an asset of the Land Bank and Land Reserves for the State to ensure an even distribution of optimization of land use, thereby creating prosperity for all Indonesian people.